Comunidades discursivas de pesquisa e educação arquivística: análise de domínio da Archival Education Research Initiative (2008-2021) - Maíra Fernandes Alencar; Natalia Bolfarini Tognoli; Brígida Maria Nogueira Cervantes (Em Questão)
In the international context, the discoursecommunity Archival Education Research Initiative, made up of faculty members and students in the field of archives, works with a focus on the educational and research dimension, guiding the debate on historically marginalized communities and how they are (under)represented in archives. Considering that this debate has also been taking place in the Brazilian context in recent years, this paper aims to characterize this discursive community based on its actors and their scientific productions.The methodology employed is exploratory and descriptive. Domain Analysis was used through two lenses: (a) epistemic, focusing on the biography of the community members, and (b) scientific production, focusing on the publications of its members in the period 2008-2021.The results were systematized along two axes: the epistemic profile, which is a biographical aspect, and the scientific structureprofile. The members’biographies cover two dimensions: research dealing with community archives, human rights, critical theory, social justice, and post-colonialism, and research dealing with archival dimensions concerning information and communication technologiesand knowledge organization.